Genome-Wide Characterization of 9-Cis-Epoxycarotenoid Dioxygenase Genes in Luffa Identifies LcNCED2 as Being Associated with ABA Levels During Seed Germination - Pingping Fang; Xifeng Li; Haoxin Mu; Jing Wei; Ting Zhang; Xueyan Wang; Qinwei Guo; Qunfeng Lou (Horticulturae)
Luffa is a genus of tropical and subtropical vines in the Cucurbitaceae family, recognized as an important cultivated commercial vegetable. However, the seeds of the luffa species are considered hard-seeded, and the processes governing seed germination remain understudied. The 9-cis-epoxycarotenoid dioxygenase (NCED) genes, which are critical for seed germination, have not been well characterized in Luffa. In this study, we identified four LaNCED genes in Luffa acutangula and four LcNCED genes in Luffa cylindrica, distributed across four chromosomes in each species. Phylogenetic analysis classified these genes into two subgroups. Gene structure and motif composition analyses revealed both similarities and differences among the NCEDs. Cis-element analysis further revealed that these NCEDs may be involved in growth regulation by modulating the phytohormonal network and responding to stress stimuli. Expression profiling of LcNCED genes during seed germination showed a decrease in LcNCED2 levels, coinciding with an increase in α-amylase activity throughout the germination process. Subcellular localization assays demonstrated that LcNCED2 is localized in the chloroplast. Furthermore, transient overexpression of LcNCED2 in tobacco leaves led to a significant increase in ABA content. Our findings provide a comprehensive genomic characterization of the NCED family in Luffa cylindrica and Luffa acutangula and reveal the functional role of LcNCED2 in regulating ABA levels, which may play a critical role in seed germination.